Práticas corporais e cristianismo: relações e preceitos - Camilo, Caio Henrique [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study, qualitative, aimed to try to understand relations and premises involving bodily practices and Christianity. The study was conducted by means of literature, focusing the themes of religion and the body along with issues involving Christian ethics, through its principles and values, which must be practiced, not only within the church, but even within the society, in sports, in schools. Based on the literature review, it can be seen that the body practices have a direct relationship with the Christian religion, in the aspects involving the ethics of their practices, experiences, thoughts, attitudes, principles and values, in addition to cultural training and body of students from different schools, in which the physical education professional is directly involved with the bodily practices. As conclusions, it was noted the probability of a harmonious and fundamental relationship between religion and bodily practices, along with a productive association between Christianity and society, helping the individual in its ethical and social formation. We suggest new approaches to the formation of the professional of Physical Education, in order take into consideration these aspects involving religiosity

Este estudo, de natureza qualitativa, teve por objetivo buscar compreender as relações e preceitos envolvendo as práticas corporais e o cristianismo. O estudo foi desenvolvido por meio de pesquisa bibliográfica, focalizando as temáticas da religião e o corpo, juntamente com questões envolvendo a ética cristã, por meio dos seus princípios e valores, os quais devem ser praticados, não somente dentro da igreja, mas, inclusive, dentro da sociedade, no meio esportivo, no âmbito escolar. Com base na revisão bibliográfica pode-se perceber que as práticas corporais possuem direta relação com a religião cristã, nos aspectos envolvendo a ética de suas práticas, vivências, pensamentos, atitudes, princípios e valores, além da formação cultural e corporal dos alunos de diversas escolas, na qual o profissional de Educação Física está diretamente envolvido com as práticas corporais. Como conclusões, notou-se a probabilidade de uma relação harmoniosa e fundamental entre a religião e as práticas corporais, juntamente com uma produtiva associação entre cristianismo e sociedade, auxiliando o indivíduo em sua formação ética e social. Sugerem-se novas perspectivas na formação do profissional de Educação Física, no sentido de levar em consideração estes aspectos envolvendo a religiosidade
Keywords: Linguagem corporal; Ética cristã; Pesquisa bibliografica; Religião e sociologia; Corpo humano; Imagem corporal